BALANCE DE LA HISTORIA CULTURAL EN CENTRO AMÉRICA. - Vega Jiménez, Patricia (2006)
The article introduces a series of reflections on the development and perspectives of the cultural history developed in the Congress VII Central American of History celebrated in Tegucigalpa, in July, 2004, emphasizing the advances and challenges that this area of the historiography has in five of the Central American countries: Panama, Costa Rica, Nicaragua, Honduras, El Salvador and Guatemala